2022
DOI: 10.1111/jar.13041
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplements for aggressive behaviour in people with intellectual disabilities: A randomised controlled crossover trial

Abstract: Background: Aggressive incidents are common in people with intellectual disabilities.Therefore, we aimed to assess whether supplementation of multivitamins, minerals, and omega-3 fatty acids (FA) reduces aggressive incidents. Methods: We conducted a randomised, triple blind, placebo controlled, single crossover intervention trial. People with intellectual disabilities or borderline intellectual functioning, between 12 and 40 years of age, and showing aggressive behaviour were included. Participants received ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In forensic psychiatric settings, it has been suggested that studies on nutritional supplementation consider the use of psychotropic medications. Recent trials on psychiatric inpatients and individuals with intellectual disabilities have proposed that the lack of beneficial effects from nutritional supplementation may be attributable to a possible ceiling effect due to the existing use of antipsychotics in most patients ( 16 , 73 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In forensic psychiatric settings, it has been suggested that studies on nutritional supplementation consider the use of psychotropic medications. Recent trials on psychiatric inpatients and individuals with intellectual disabilities have proposed that the lack of beneficial effects from nutritional supplementation may be attributable to a possible ceiling effect due to the existing use of antipsychotics in most patients ( 16 , 73 ).…”
Section: Discussionmentioning
confidence: 99%
“…To address these nutrient deficiencies, some randomized controlled trials (RCTs) have found broad-range supplements that comprise various vitamins, minerals, and macronutrients to be associated with reductions in aggressive and rule-breaking behavior in children with ADHD ( 10 ) and conduct problems ( 11 ), and in incarcerated samples ( 12 14 ). Others, however, reported that multivitamin, mineral, and omega-3 supplementation did not significantly reduce aggressive incidents in psychiatric inpatients ( 15 ) or in aggressive individuals with intellectual disabilities ( 16 ). The finding that very few studies examined the same composition of nutritional supplementation has resulted in a call for investigations of supplement content and dosage ( 17 ).…”
Section: Introductionmentioning
confidence: 99%